Ukrainian social and domestic fairy tale: the dynamics of the tradition folklore consciousness (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article deals with functional traditional features of consciousness in folklore, represented by the Ukrainian folk tales of everyday life. Particular attention was paid to semantic transformation of social and living codes.
Keywords: социально-бытовая сказка; фольклорное сознание; код